Field of Study and Family Outcomes - Elisabeth Artmann; Nadine Ketel; Hessel Oosterbeek; Bas van der Klaauw (Institute of Labor Economics (IZA), 2018)
This paper uses administrative data from 16 cohorts of the Dutch population to study the relationship between field of study and family outcomes. We first document considerable variation by field of study for a range of family outcomes. To get to causal effects, we use admission lotteries that were conducted in the Netherlands to allocate seats for four substantially oversubscribed studies. We find that field of study matters for partner choice, which for women also implies an effect on partners' earnings. Fertility of women is not affected and evidence for men is mixed, but we find evidence for intergenerational effects on children's education. This means that field of study does not only affect individual labor market outcomes but also causally influences other important dimensions of a person's life.
Keywords: I26; J12; J13; 330; higher education; study choice; returns to education; assortative matching; intergenerational mobility